(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
Communicative foreign language instruction is one of the key components of the modernization of Uzbek education concept. The construction and development of future specialists with communicative language competency is the goal of the required "Foreign language" discipline in the state-mandated vocational education system. The development of students’ communicative language abilities will enable them to participate in professional foreign language communication, recognize their personal and professional demands, and take advantage of business relationships that offer opportunities for professional growth and self-education.